Obtenção e avaliação de compósitos à base de resíduo de gesso e poliestireno expandido (EPS) - Gasparin, Paula Graziela (2020)
The production of solid waste in countries such as Brazil grows annually and civil construction is responsible for much of the consumption of materials for the production of goods, resulting in the generation of high volumes of construction and demolition waste (CDW). Reuse and recycling are of interest in waste management and management, especially in the context of circular economy, closing the life cycle. In this context, this work aimed to study the effect of the gradual incorporation of Styrofoam waste (EPS) in a matrix of gypsum waste from civil construction, evaluating the physical, mechanical and acoustic properties of composites. For that, the incorporation of five quantities of residual EPS (0; 0.5; 1.0; 1.5 and 2.0 grams) in gypsum residue matrixes was evaluated, evaluating the properties in the fresh and hardened state of the composites, for a water/gypsum ratio of 0.6. Physical and mechanical properties were studied, such as density, compressive strength, hardness and dynamic elastic modulus with and without temperature variation effect. Finally, the acoustic properties of boards made from gypsum and Styrofoam residue composites were studied, analyzing their noise absorption performance. The results indicated that the gradual incorporation of Styrofoam waste improved the acoustic properties and brought more lightness to the composite, however, the mechanical properties decreased as the addition of Styrofoam increased. The composite developed employs two industrial wastes (EPS and gypsum) and may be of interest in sustainable projects, in applications where there is a need to use materials with low density and/or acoustic insulation.